ANALISIS PENGELOLAAN WAKAF UANG MELALUI CASH WAQF LINKED SUKUK DALAM MENINGKATKAN PEMBERDAYAAN MASYARAKAT DI BWI - Larasati Dhinarti Nurresi Putri (2021)
Understanding of Muslims when hearing the term waqf tends to refer to waqf of fixed assets such as land, even though there are other waqf instruments, namely cash waqf. Cash waqf is financial instrument that is flexible and easily accessible so it has great potential in empowering community. In increasing potential of cash waqf, government launched Cash Waqf Linked Sukuk (CWLS), namely waqf-based Sukuk investment. CWLS instrument has potential to optimize unproductive waqf assets into productive ones. This research aims to identify and analyze cash waqf management system and management of CWLS program in improving community empowerment at Indonesian Waqf Board (BWI). This research uses descriptive qualitative method with case study approach, starting with interviewing BWI and Achmad Wardi Eye Hospital. Then to prove validity of research data, researcher used technique triangulation method. Furthermore, researcher analyzed data by doing data reduction, data presentation, and concluding. The results of research show that management of cash waqf carried out by BWI is quite diverse so that scopes becomes wide. Management of CWLS has been running according to set plan, but not all CWLS programs are run by BWI, there are several programs whose benefits are distributed to nazhir institutions registered by BWI.